Occurrence of new neurons in the piriform cortex - Yuan, Ti-Fei; Liang, Yu-Xiang; So, Kwok-Fai (Frontiers in Neuroanatomy, 2015)
Adult neurogenesis has been well studied in hippocampus and subventricular zone; while this is much less appreciated in other brain regions, including amygdala, hypothalamus and piriform cortex. The present review aims at summarizing recent advances on the occurrence of new neurons in the piriform cortex, their potential origin and migration route from the subventricular zone. We further discuss the relevant implications in olfactory dysfunction accompanying the neuro-degenerative diseases.